Lived experience of patients on tuberculosis treatment in Tshwane, Gauteng province - Oluwafunmilayo O. Akeju; Susanna C.D. Wright; Todd M. Maja (AOSIS, 2017)
Tuberculosis is one of the communicable diseases that still contributes substantially to the worldwide disease burden and is still a major health threat worldwide. In order to gain abetter understanding of being a patient taking tuberculosis treatment and to improvead herence to treatment, this phenomenological study was conducted to explore the lived experience of patients on tuberculosis treatment.The population comprised patients in an identified tuberculosis clinic in Tshwane who had been on treatment for at least four months and who were able to communicate in English. The data gathering instrument was self-report by in-depth interview. Some of the main themes that emerged include influence of personal social situation, influence of good social support and disclosure, experience of taking medication daily and knowledge about tuberculosis treatment.Findings revealed that the personal social situations of the participants which include accommodation, unemployment and nutritional requirements influenced the adherence of the participants to treatment. It was discovered that good social support had an influence on adherence which could only be enjoyed when the treatment and diagnosis of tuberculosis is disclosed to the family members and friends. Some of the participants, who had been non adherentin the past, attributed the reasons for their non-adherence to the side effects that they experienced. Lastly, participants also reported knowledge about tuberculosis, that is, knowledge about its causes, treatment and prevention, as crucial for adherence to treatment.